Only social feedback reduces age-related prospective memory deficits in "Virtual Week". (May 2014) - Niedźwieńska, Agnieszka; Rendell, Peter G.; Barzykowski, Krystian; Leszczyńska, Alicja
ABSTRACT Background: Prospective memory, or remembering to do things in the future, is crucial for independent living in old age. Although there is evidence of substantial age-related deficits in memory for intentions, older adults have demonstrated the ability to compensate for their deficits in everyday life. The present study investigated feedback as a strategy for facilitating prospective memory in the elderly. Method: Young and older adults played a computer-based task, Virtual Week, in which they had to remember to carry out life-like intentions. After each virtual day, specific feedback on prospective memory performance was automatically provided on the computer screen that participants either proceeded through by themselves (non-social feedback) or were taken through by an experimenter (social feedback). The control group received no feedback. Results: We found that, compared with no-feedback group, only social feedback substantially reduced the age-related deficit in prospective memory. Older adults significantly benefited from feedback provided by the experimenter on the tasks of intermediate difficulty. Unexpectedly, prospective memory with non-social feedback was not only worse than with social feedback, but it was not any better than without any feedback at all. Conclusions: The results extended previous findings on the effectiveness of feedback in improving the memory performance of older adults to include memory for intentions. Despite the feedback meeting the critical recommendations of being specific, objective, and well-targeted, it was ineffective when the feedback displayed on the computer was not introduced by the experimenter. This has implications for computerized training tasks where automated feedback is considered crucial.